Types of economic theory : from mercantilism to institutionalism - Mitchell, Wesley C. (New York : A. M. Kelley, 1967)
The book covers: The study of the Economic Classics; Adam Smith and How Political Economy Came to be Systematized in England; Jeremy Bentham and the Utilitarian Creed; Thomas Robert Malthus and the Empirical Trend; David Ricardo and the Making of Classical Political Economy; The New Social Sciences at Work: The Philosophical Radicals; Political Economy in the Days of its Triumph and John Stuart Mill and Humanization of Classical Economics.
Published in 1949 under title: Lecture notes on types of economic theory.
Includes bibliographical footnotes.
rpm 04/07/2017
Loans
Keywords: Economics